2017
DOI: 10.2116/analsci.33.519
|View full text |Cite
|
Sign up to set email alerts
|

Validation of in situ Measurements of Atmospheric Nitrous Acid Using Incoherent Broadband Cavity-enhanced Absorption Spectroscopy

Abstract: Incoherent broadband cavity-enhanced absorption spectroscopy (IBBCEAS) is a useful technique for measuring trace gaseous species in the atmosphere. Recently, IBBCEAS was used to measure concentrations of nitrous acid (HONO) in the troposphere to resolve controversies related to its formation and loss. Here, measurements of HONO and a mixture of HONO and NO2 using IBBCEAS were validated by comparing them with those obtained with a NOx analyzer. Good agreement was found between these methods, given their respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…The combination of mirror reflectivity and cavity length produced path length of 6 km from a 1 m long cavity, i.e., better than most works, with the exception of Gherman et al (2008), who used a longer cavity (4.5 m) to achieve a path length enhancement of 7.5 km, and the work of Scharko et al (2014), who used slightly more reflective mirrors (99.986 % vs. this work's 99.981 %) and a cavity of approximately the same length. The 60 s HODOR LOD was 240 pptv and of similar magnitude to the LODs of 180 pptv reported by Duan et al (2018) and of 200 pptv reported by Nakashima and Sadanaga (2017) and are hence on par with state-of-the-art instruments.…”
Section: Discussionsupporting
confidence: 74%
“…The combination of mirror reflectivity and cavity length produced path length of 6 km from a 1 m long cavity, i.e., better than most works, with the exception of Gherman et al (2008), who used a longer cavity (4.5 m) to achieve a path length enhancement of 7.5 km, and the work of Scharko et al (2014), who used slightly more reflective mirrors (99.986 % vs. this work's 99.981 %) and a cavity of approximately the same length. The 60 s HODOR LOD was 240 pptv and of similar magnitude to the LODs of 180 pptv reported by Duan et al (2018) and of 200 pptv reported by Nakashima and Sadanaga (2017) and are hence on par with state-of-the-art instruments.…”
Section: Discussionsupporting
confidence: 74%
“…For HONO measurement, the reported IBBCEAS device is in a spectral range of 360–375 nm using UV LED. In 2017, Nakashima et al [ 63 ] reported an IBBCEAS set-up based on a UV-LED for HONO detection, with a 50 cm-long cavity formed by two mirrors ( R ~99.985%). A MDL of 0.2 ppbv for HONO was achieved in a 5 min acquisition time.…”
Section: Target Gas Species Performances In Laboratorymentioning
confidence: 99%
“…HONO detection methods are mainly classified into two categories: one is based on wet chemical techniques, and the other is based on spectroscopic methods. The wet chemical methods mainly include denuder absorption-ion chromatography (Denuder-IC; Neftel et al, 1996), gas and aerosol collector (GAC) systems (Dong et al, 2012), stripping coilion chromatography (SC-IC; Xue et al, 2019;Cheng et al, 2013), and long-path absorption photometry (LOPAP;Chen et al, 2014;Heland et al, 2001;Kleffmann et al, 2006). These kinds of methods have a lower detection limit and can reach several parts per trillion by volume.…”
Section: Introductionmentioning
confidence: 99%